SUN-097 AgRP Neurons Determine Survival in Activity-Based Anorexia Model - Miletta, Maria Consolata; Shanabrough, Marya; Sestan-Pesa, Matija; Varela, Luis; Mancini, Giacomo; Spadaro, Olga; Zeiss, Caroline; Dixit, Vishwa; Dietrich, Marcelo; Horvath, Tamas (Journal of the Endocrine Society, 2019)
Anorexia Nervosa (AN) is an eating disorder characterized by severe hypophagia, high levels of physical activity, harsh weight loss and an intense fear of weight gain. It has the highest mortality rate among psychiatric illnesses and, due to the unknown underlying neurobiology, it is challenging to treat. Agouti-related protein (AgRP) neurons, which are localized in the arcuate nucleus in the hypothalamus, are both necessary and sufficient or feeding in adult animals.To uncover new neural circuits that may contribute towards vulnerability to AN or might be affected by AN, we employed the specific diphtheria toxin receptor-expressing mice (AgRP-DTR) which, by the selective ablation of AgRP neurons, allow to test the impact of an impaired AgRP circuit function under the activity-based anorexia (ABA) paradigm. ABA is a bio-behavioral phenomenon described in rodents and refers to the weight loss, hypophagia and paradoxical hyperactivity that develops in rodents exposed to running wheels and restricted food access, and provides a model for the key symptoms of AN. Mice that express DTR only in AgRP neurons and subcutaneously injected with diphtheria toxin (DTX) at postnatal day 3 lost more than 50% of AgRP neurons on postnatal day 7 compared to control. The same percentage of neuronal loss was detected in 8 weeks old mice. In addition, the neonatal animals developed normally after AgRP ablation, did not show any phenotypic effects and maintained normal food intake and weight when fed ad libitum. On postnatal day 36 (P36), males and females animals were housed with access on a running wheel and fed ad libitum for 4 days (acclimation phase). On P40, for 72 hours animals were fed for only two hours daily. Following the fasting phase, free access to food was returned and the running wheel was removed. Continuous multi-day analysis of running wheel activity showed that both controls and AgRP-DTR mice kept constant weight and food intake during acclimation. In contrast, although mice became hyperactive within the 24 hours following the onset of food restriction (FR), we noted a 10% mortality on day 2 and 70% mortality at day 4 among the AgRP DTR mice. Moreover, the survived AgRP-DTR mice failed to return to normal food intake and weight even when ad libitum food was provided. Overall, AgRP neurons showed to be crucial for the full development of ABA symptoms. The results suggest that our new experimental setting is able to correlate particular neurons populationto vulnerability, onset and progression of anorexia nervosa.